Analisis Kesadaran Masyarakat Indonesia Tentang Pentingnya Asuransi Syariah - Siska Permata Sari Harahap; Zainarti Zainarti (STIKes Ibnu Sina Ajibarang, 2025)
The aim of this research is to determine the level of public awareness Indonesian people regarding the importance of sharia insurance. Even though there is an increase in public interest in sharia insurance, with data showing a about 39% increase in comprehension between 2016 and 2020, the level of awareness is still relatively low. This results from a failure to comprehend the basic principles of sharia insurance, lack of access to effective education and outreach, and distrust of sharia financial institutions. This research found that the millennial generation shows greater interest in sharia insurance, However, many people still do not know the distinction between conventional and sharia law insurance. Therefore, more intensive efforts are needed to increase sharia financial literacy and inclusion through comprehensive education programs. This research recommends stakeholders to develop more effective strategies in increasing sharia insurance penetration and building public awareness about the importance of insurance in everyday life. Thus, increasing public awareness and understanding of sharia insurance is expected to expand sharia financial inclusion and provide broader benefits for society and the Indonesian economy.